VD_FINDINFO Décision / 2014 / 23 vom 9. Januar 2014 - VD Tribunal cantonal (2014)
DÉTENTION PRÉVENTIVE, RISQUE DE FUITE, RISQUE DE COLLUSION | 221 al. 1 let. a CPP (CH), 221 al. 1 let. b CPP (CH), 393 al. 1 let. c CPP (CH)